Analytical Journalism : A Guide to Science based Exp.lanatory Journalistic p.ratice (new york;london : Routledge Taylor and Francis Group., 2024)
Resp.onding to an increasingly comp.lex and often contradictory barrage of news information Analytical Journalism offers first of its kind guide to this emerging orm of science based journalism
INDEX/p..208-2012
Keywords: analytical journalisme; Science based Exp.lanatory Journalistic